Efektivitas Bokashi Fermentasi Feses Ayam untuk Pertumbuhan Tanaman Jagung Manis (Zea mays saccharata Sturt) - Siti Ainun Rofiah Ainun; Siti Roudlotul Hikamah; Haning Hasbiyati (JURNAL BIOSHELL, 2022)
ABSTRACT Sweet corn (Zea mays saccharata Sturt) is a commodity that can be used as food grocery. Generally, farmers cultivate the sweet corn using pesticide fertilizers as the main fertilizer without organic fertilizers as the balancing composition. However, if this process has been done in long time, it will cause an environmental pollution. Organic fertilizer is a relevant solution to substitute inorganic fertilizers, for instance bokashi. This research was aimed to determine the effectiveness of using fermented chicken feces bokashi for the growth of sweet corn. This experimental research uses a completely randomized design (CRD) with 3 factorial patterns. The results from one way ANOVA on sweet corn were obtained: 1) the calculated F value was 24,980 with the significance value is 0.000 for plant height; 2) the calculated F value is 18.646, the significance value is 0.000 for number of leaves; 3) the calculated F value is 43,842 and the significance value is 0.000 on the stem diameter. Thus, it can be concluded that the treatment with bokashi indicated a significant effect on the growth of sweet corn. The results of Duncan's test showed that the treatment with bokashi had a significant difference for the growth of sweet corn. It was caused by the addition of organic composition from bokashi that can increase the content of organic composition and nutrients in the soil. In addition, bokashi has advantages that the other two treatments do not have, against caterpillars and rats. The content of bokashi can protect sweet corn in the vegetative to generative phase. At the 56th day, it resulted the presence of rat caterpillar pests on sweet corn fruit given by NPK fertilizer treatment and negative control (without treatment). Keywords: bokashi, growth, sweet corn